IMPLEMENTASI KEBIJAKAN REFOCUSING ANGGARAN PENDAPATAN DAN BELANJA DESA DI KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - Kasenda, Luki Gerard Johannes; Pioh, Novie R.; Kimbal, Alfon (Sam Ratulangi University, 2022)
The purpose of this study was to analyze the Implementation of the Refocusing Policy on the Village Budget for Fiscal Year 2020 in Kawangkoan Barat District, Minahasa Regency, especially in Kayuuwi Satu Village, Kanonang Lima Village and Tombasian Bawah Village. The research method used in this study is a qualitative research method. The data used are primary data and secondary data, data collected through interview and documentation mechanisms. The data were analyzed qualitatively by going through 4 (four) stages, including: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Central Government's policy of making the village expenditure revenue budget to assist in handling the impact of Covid-19 in the village is appropriate and there is a need for other programs besides providing assistance to the community. In addition, the understanding of the size and purpose of the policy of refocusing the village income and expenditure budget in the 3 villages that are the focus of the research is good and understood by implementing actors in the field.